Board characteristic and corporate environmental reporting in Nigeria - Usman Shehu Aliyu (Emerald Publishing Limited, 2018)
The issue that revolves around corporate governance and corporate environmental reporting (CER) has always been an essential element deliberated upon globally. A good corporate governance mechanism instills an investor’s confidence and ensures a transparent process that facilitates more disclosures and quality reporting. Precisely, the purpose of this paper is to investigate the relationship between corporate governance variables, namely, board size, board independence, board meeting (BM), risk management committee composition and CER in Nigeria. This study utilized the data obtained from the annual reports of 24 non-financial public listed companies in the Nigeria Stock Exchange comprising three sectors, namely, industrial goods, natural resources and oil & gas for the period of 2011–2015. The model of this study is theoretically based on agency theory. In analyzing data, this study utilized panel data analysis. Based on the Hausman test, the random effect model was used to examine the effect of predictors on CER. The result indicates a positive significant relationship between board independence and CER. Similarly, a positive significant relationship between BM and CER is revealed in the study. However, there is no significant relationship between other hypothesis variables and CER. Finally, the study provides suggestions for future research and several recommendations for regulators, government and accounting professional bodies.The data was analysed using statistics.The result indicates a positive significant relationship between board independence and CER. Similarly, a positive significant relationship between BM and CER is revealed in the study. However, there is no significant relationship between other hypothesis variables and CER.There are no prior studies linking risk management committee with CER.